Antecedents of Rape Cases Exposure Over Social Media: A Comparative Study of Urban and Rural Areas of Lahore District - Dr. Aemen Khalid; Sidra Charles; Dr. Zaeem Yasin; Maham Tallat (Journal of Management Practices, Humanities and Social Sciences, 2021)
The goal of this study is to determine the effects of rape case's exposure over social media. The researcher has observed the changes among users who are going through the exposure of rape cases in this research. The present study is based on the quantitative approach in which the researcher has selected the survey method as a tool to explore and investigate the consequences of rape cases exposure among users. The data was collected through a questionnaire. The questionnaires were distributed in five different tehsils of Lahore (Lahore Cantt, Raiwind, and Lahore City, Shalimar, and Model town) including both urban and rural areas using conveniencesampling technique. The data were analyzed through SPSS using regression and chi-square techniques. One hundred participants from each tehsil were assigned to complete several surveys regarding rape cases exposure. This research focused on the selected effects of rape case exposure like anxiety, phobia, fear, depression, frustration, and mental illness problems. Results indicate that any person who has more exposure to rape cases has more effect on the user’s mental state. Upon mining such data on Facebook, Instagram, and Twitter, some privacies and securities to control the negative exposure over social media and the government should develop a strict law and order situations and check the calculations highlighted in the thesis that the subject matter has become serious. The researcher will suggest that the punishments from an Islamic point of view are the perfect solution to the problem of raping young girls and children.